2022
DOI: 10.1186/s13613-022-01070-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting responders to prone positioning in mechanically ventilated patients with COVID-19 using machine learning

Abstract: Background For mechanically ventilated critically ill COVID-19 patients, prone positioning has quickly become an important treatment strategy, however, prone positioning is labor intensive and comes with potential adverse effects. Therefore, identifying which critically ill intubated COVID-19 patients will benefit may help allocate labor resources. Methods From the multi-center Dutch Data Warehouse of COVID-19 ICU patients from 25 hospitals, we sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They found that the PaO 2 /FiO 2 improvement was significant between responders and non-responders which was concurrent with our findings. 12 14 Guerin et al concluded that though PPV improves oxygenation and ventilation and reduces mortality, there was no association between them. 7 , 33 This infers that the better prognosis in ARDS patients receiving PPV is due to the ability of PPV to reduce VILI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the PaO 2 /FiO 2 improvement was significant between responders and non-responders which was concurrent with our findings. 12 14 Guerin et al concluded that though PPV improves oxygenation and ventilation and reduces mortality, there was no association between them. 7 , 33 This infers that the better prognosis in ARDS patients receiving PPV is due to the ability of PPV to reduce VILI.…”
Section: Discussionmentioning
confidence: 99%
“…With this background, we aimed to determine the changes and the role of DP as compared to improvement in oxygenation (PaO 2 /FiO 2 ) at different time points as predictors of mortality outcomes in moderate-severe ARDS patients with PPV. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Second, the introduction of a complex clinical tool using machine learning, assessment of statistical interactions and other sophisticated mathematical tools would not have been feasible in 1996. Conversely, the current availability of smartphones, much more powerful than personal computers means there is great potential for the creation of new prognostic tools and this should be considered when the decision is made to update the SOFA score [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…ML flexibility detects relationships between potential clinical features, physiologic parameters, and an outcome [ 13 ]. Despite extensive modeling and a large number of clinically relevant features, the discrimination using ML approaches for predicting responders to the prone position in mechanically ventilated patients with COVID-19 [ 14 ] was very poor. Scarce studies have evaluated the role of ML in predicting the duration of MV in ARDS patients [ 11 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%